The Effect of Entrepreneurial Marketing Perceptions on MSMEs Business Performance During Covid-19 Pandemic in Bogor City - Rinda Tri Wijayanti; Mukhamad Najib; Mimin Aminah (School of Business, IPB University (SB-IPB), 2022)
This study aims to analyze the factors that affect the business performance of Micro, Small and Medium Enterprises (MSMEs) during the COVID-19 pandemic in Bogor City. The research was carried out during January-February 2021 on 150 MSME respondents with the criteria of a food processing business, a minimum business age of 2 years or have opened a business before the pandemic period. The data processing method employed in the form of quantitative descriptive analysis, cross-tabulation and using the SEM-PLS. The results showed that the characteristics of the business doers described by gender, age, educational background, reasons for pursuing a business, initial work before starting a business, the beginning of running a business, length of business which reflected by age and education level had a correlation with production techniques on internal environmental factors. External environmental factors have a significant positive effect on entrepreneurial marketing and performance which are explained by government policy aspect, socio-cultural and economic aspect, role of related institutions aspect and aspect of competitors, from these indicator variables, socio-cultural and economic aspects most reflect the external environment from the business doers. Internal environmental factors have a positive and significant effect on entrepreneurial marketing, but on the contrary, the higher the internal environmental factors, the lower the business performance. Entrepreneurial marketing shows a significant and positive influence on the business performance of MSMEs in Bogor City with a proactive indicator that can reflect entrepreneurial marketing, while business performance is reflected by the customer growth indicator. Keywords: business performance, business environment, COVID-19 pandemic, entrepreneurial marketing, MSMEs